Accuracy of echocardiography and ultrasound protocol to identify shock etiology in emergency department - Asmaa Ramadan; Tamer Abdallah; Hassan Abdelsalam; Ahmed Mokhtar; Assem Abdel Razek (BMC Emergency Medicine, 2022)
Abstract Background Early diagnosis and appropriate management of shock aimed at prevention of prolonged hypoperfusion has shown to decrease morbidity and mortality in patients with undifferentiated shock. However, there is often a challenge in emergency department (ED) – where diagnosis is mainly based on clinical signs and standard monitoring parameters. Early use of point of care ultrasound could reduce the diagnostic time and improve diagnostic accuracy. Purpose The aim of this study is to investigate the accuracy of echocardiography - ultrasound protocol to identify the cause of shock in ED. Method The study was conducted on 150 shocked patients admitted to emergency department of Alexandria Main University Hospital from December 2018 to December 2020. The study was conducted to reach initial impression about shock etiology which was then compared to final diagnosis to determine accuracy, agreement, sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV). Results One hundred forty patients were included in the study (10 patients were excluded). The protocol was 100% accurate for diagnosing cases with obstructive and mixed obstructive distributive shock. It showed excellent rule- out characteristics for cardiogenic shock (sensitivity and NPV = 100%). There was almost perfect agreement between provisional and final shock type for mixed distributive cardiogenic shock (kappa 0.915). Echo- US protocol had lowest agreement and PPV for patients with hypovolemic shock Kappa 0.48 and 35% respectively. Conclusion The Echo- US protocol showed a high accuracy in identifying shock etiology in ED and is likely a promising diagnostic tool in emergency care.